Checklist of host associations of European bat flies (Diptera: Nycteribiidae, Streblidae) - Szentiványi, Tamara; Estók, Péter; Földvári, Mihály (Zootaxa, 2016)
Bat flies are obligate blood-sucking ectoparasites of bats. They are divided into two families: Nycteribiidae and Streblidae. Europe has 17 species of bat flies and 45 species of bats (Mammalia: Chiroptera). This checklist is based on both published records and our own field data and provides updated information on all associations between bat flies and their hosts in Europe. The host-parasite association between Basilia italica Theodor and Plecotus auritus (Linnaeus) is reported for the first time. Moreover, our records of B. italica on Myotis alcathoe Helversen & Heller, B. nana Theodor & Moscona on Plecotus auritus, Nycteribia kolenatii Theodor & Moscona on M. bechsteinii (Kuhl) and Penicillidia dufourii (Westwood) on M. daubentonii (Kuhl) represent new host associations for Hungary.